Cracks in the Ceiling? Historical and Contemporary Trends of African American Deans of Schools of Social Work. (March 2018) - Banks, Leon; Hopps, June Gary; Briggs, Harold E.
This article presents data from an exploratory study of the demographic and published scholarship profiles of the deans and university provosts of the top 50 schools of social work as ranked by the 2016 U.S. News and World Report ratings. Method: The authors used an exploratory design to conduct a content analysis of the demographic and scholarship characteristics of the deans and provosts of the 50 top schools of social work. Results: The data show that the majority of deans and provosts of the top 50 schools of social work are Caucasian. The frequency of mentions of African Americans and other ethnically diverse groups in published articles by deans is uneven. Implications: This study highlights recommendations to enhance the opportunities for deanships among racially diverse faculty and to guide further research that explores the reasons for lack of racially diverse candidates selected as deans of schools of social work.